Progression of oral squamous cell carcinoma accompanied with reduced E-cadherin expression but not cadherin switch. - Takashi Hashimoto; Yuichi Soeno; Genta Maeda; Yuji Taya; Takaaki Aoba; Masanori Nasu; Shuichi Kawashiri; Kazushi Imai (PLoS ONE, 2012)
The cadherin switch from E-cadherin to N-cadherin is considered as a hallmark of the epithelial-mesenchymal transition and progression of carcinomas. Although it enhances aggressive behaviors of adenocarcinoma cells, the significance and role of cadherin switch in squamous cell carcinomas (SCCs) are largely controversial. In the present study, we immunohistochemically examined expression of E-cadherin and N-cadherin in oral SCCs (n = 63) and its implications for the disease progression. The E-cadherin-positive carcinoma cells were rapidly decreased at the invasive front. The percentage of carcinoma cells stained E-cadherin at the cell membrane was reduced in parallel with tumor dedifferentiation (P<0.01) and enhanced invasion (P<0.01). In contrast, N-cadherin-positive cells were very limited and did not correlate with the clinicopathological parameters. Mouse tongue tumors xenotransplantated oral SCC cell lines expressing both cadherins in vitro reproduced the reduction of E-cadherin-positive carcinoma cells at the invasive front and the negligible expression of N-cadherin. These results demonstrate that the reduction of E-cadherin-mediated carcinoma cell-cell adhesion at the invasive front, but not the cadherin switch, is an important determinant for oral SCC progression, and suggest that the environments surrounding carcinoma cells largely affect the cadherin expression.